8-Shaped Inductors: An Essential Addition to RFIC Designers’ Toolbox - Pingda Guan; Haikun Jia; Wei Deng; Teerachot Siriburanon; Robert Bogdan Staszewski; Zhihua Wang; Baoyong Chi (IEEE Open Journal of the Solid-State Circuits Society)
The rapidly advancing field of millimeter-wave (mm-wave) radio-frequency integrated circuit (RFIC) design has ushered in an era of remarkable innovation, particularly in the realm of on-chip passive devices. Among them, 8-shaped inductors have emerged as a novel and promising variant, attracting significant research interest thanks to their unique geometry and electromagnetic (EM) properties. The distinctive feature of 8-shaped inductors lies in their antiparallel magnetic fields due to the opposing current flows within the two turns, enabling manifold applications. In this article, we comprehensively explore the 8-shaped inductors with a focus on their diverse utilizations, including EM interference (EMI) reduction, compactness of RF layout, provision for a magnetic feedforward/feedback arrangement, and oscillation mode manipulation, thereby demonstrating that the 8-shaped inductor can be an essential addition to RFIC designers’ toolbox.